2022
DOI: 10.3390/jcm11113236
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-Year Differences in Indications for Cardiac Resynchronization Therapy in International Guidelines—Insights from the Heart Failure Registries of the European Society of Cardiology

Abstract: Cardiac resynchronization therapy (CRT) applied to selected patients with heart failure (HF) improves their prognosis. In recent years, eligibility criteria for CRT have regularly changed. This study aimed to investigate the changes in eligibility of real-life HF patients for CRT over the past fifteen years. We reviewed European and North American guidelines from this period and applied them to HF patients from the ESC-HF Pilot and ESC-Long-Term Registries. Taking into consideration the criteria assessed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The magnitude of the problem varies based on eligibility criteria and population selection. 13 , 14 Lund et al 15 reported that CRT underutilization varies, depending on different consistency analyses, from 69 to 79% based on class I and IIa indications from 2013 EHRA. Linde et al 16 estimated that two-thirds of eligible HFrEF patients were not receiving CRT.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the problem varies based on eligibility criteria and population selection. 13 , 14 Lund et al 15 reported that CRT underutilization varies, depending on different consistency analyses, from 69 to 79% based on class I and IIa indications from 2013 EHRA. Linde et al 16 estimated that two-thirds of eligible HFrEF patients were not receiving CRT.…”
Section: Discussionmentioning
confidence: 99%
“…If they respond to inotrope therapy, CRT could possibly delay or replace advanced heart failure therapies such as left ventricular assist devices or transplantation. Guidelines have changed significantly in the last 15 years [15]. Diminished renal function is a comorbidity that is associated with poor outcome in heart failure and might hamper the benefit of CRT [16].…”
mentioning
confidence: 99%